Accompaniment of Village Library Development in Grajagan Village, Purwoharjo District, Banyuwangi Regency - Hari Siswoyo; Dwi Priyantoro; M. Taufiq; Andre P. Hendrawan; Eri Widayanti (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2021)
The Grajagan village had a library located at the village office. So far, the library has not been managed and utilized optimally. The problems that occur in this library include the lack of book collections, the absence of chairs and tables for readers, the condition of the library is not well organized, and the library staff were not trained in managing the library. These problems have resulted in the low interest of the people of Grajagan village to visit the village library. To solve the problems, it was necessary to provide assistance in library development. Library development is carried out through the addition of book collections, providing chairs and tables for readers, arranging library space, and training for library staff. Based on the results of community service activities that have been carried out, it can be stated that the library's book collection has increased by 88 books, the library space becomes more comfortable with the increase in furniture, and the library staff has increased their knowledge in terms of library management. To further increase the role and function of the library, promotion or introduction to the library's book collections and facilities to local villagers is required.